Penerapan Kompres Hangat Terhadap Nyeri Dismenore Pada Siswi Kelas VII Dan VIII SMP - Reni Trevia; Ira Sri Budiarti; Eliwarti (Jurnal Amanah Kesehatan, 2023)
Based on the initial survey interview conducted on April 10 2023, which was conducted with 10 female students at Baiturrahmah Padang Middle School, 5 of them said that they experienced dysmenorrhoea with a moderate level of pain and none had reduced the pain with warm compresses. The impact of dysmenorrhoea in teenagers is that it can interfere with learning and daily activities. The aim of the research was to determine how to reduce the intensity of dysmenorrhea pain between warm compresses and cold compresses in junior high school students. This type of pre-experimental research uses a One Group Pretest-Posttest design approach. The research was carried out from March – August 2023. Univariate and bivariate analysis of the results used the paired T-test statistical test. The sample in this study was 10 people using a purposive sampling technique. Keywords: dismenorhea; warm compress